PENGARUH PELATIHAN, DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Pada Otoritas Jasa Keuangan Regional 3 Surabaya) - Bayuaji, Rizal Bima; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2015)
This study was based on Financial Services Authority needsâ€™ of high productivity as a new-born body. Financial Services Authority (OJK) as a financial services monitoring body in Indonesia is important to note as a support to OJK,s existence. This study aimed to examine the effect of training, work discipline, and leadership to employeesâ€™ productivity in OJK Regional 3 Surabaya. This study used purposive sampling method with a sample of 93 people from a population of employees in OJK Regional 3 Surabaya. The analytical method used is multiple linear regressions. The results of the study found that the following regression equation: Y = 0.499 X1 + 0.426 X2 Â + 0.355 X3. Based on statistical data analysis, the indicators in this study were valid and reliable. In the classical assumption test, regression model was free from multicolonearity, no heteroscedasticity, and normal distribution. The greatest variable was training variable which equaled to 0.499, while the smallest variable is leadership which equaled to 0,355. The results of the study found that all independent variables were positive and had a significant effect on the dependent variable.